EVALUATION OF WASTE MANAGEMENT POLICY IN ACEH PROVINCE'S LANDFILL - Saharuddin (RADJA PUBLIKA, 2026)
management can lead to environmental pollution. This condition results in a decline in environmental quality and harms human health. One of the negative impacts of waste can arise from the source, where waste producers fail to properly handle waste. Research findings, including the limited number of human resources for landfill management, limited institutional frameworks for budget management, and the limited number of regional regulations established to support waste management policies in Aceh Province, indicate that waste management policies in Aceh Province still do not meet the criteria for adequacy as a public policy. The coverage of waste management services has only reached 66.73%, indicating that the Waste Management Policy at landfills in Aceh Province still does not meet the criteria for